Peculiarities of digital learning means usage in training future computer science teachers of «programming languages» course - Нікольський, С. Б.; Сирчина, С. В. (Scientific notes of the pedagogical department, 2019)
The ar cle highlights the peculiari es of the use of digital learning means in the teaching of the discipline “Programming languages”. The authors analyzed the experience of using the command line en-vironment when teaching programming in a higher educa on ins tu on. The emphasis focuses on ana-lyzing the possibili es for students to use the command line of the opera ng system (OS) in the process of crea ng their curricula with a graphical interface and ordinary programs in the educa onal environment of a higher educa on ins tu on. It is noted that in the process of teaching programming with the help of the command line of an OS in front of the educators a complex task is being put. In the process of its solu on, students independently search for the necessary source data and form the basis for the crea on and se ng-up of the program, foresee the results of the program implementa on, choose the strategy of using the general didac c pro-gramming so ware with modern and neoteric informa on technologies, perform tasks and analyze the quality of its execu on, and accordance with expected results. It is stated that students perform their task while designing an applica on that is embedded in an HTML page using a special tag. The graphic primi ve program code is loaded and executed using digital learning tools. The authors described the stages of crea ng educa onal programs using resources and tools of the Java Development Kit (JDK) and OS, highlighted the peculiari es of the implementa on and expediency of using applets in programming graphics in the educa onal process using the original source code of the program with graphic primi ves as an example. Scien fic research contains recommenda ons for using the command line to develop simple educa-onal applica ons with a graphical interface. The ar cle outlines the advantages of digital learning tools in teaching programming, namely the command line of an OS and the usual didac c so ware.